2017
DOI: 10.1016/j.envres.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension among adults exposed to drinking water arsenic in Northern Chile

Abstract: Background A growing number of studies have identified an association between exposure to inorganic arsenic and hypertension. However, results have not been consistent across studies. Additional studies are warranted, given the global prevalence of both arsenic exposure and morbidity attributable to hypertension. Methods We analyzed data collected from October 2007–December 2010 for a population-based cancer case-control study in northern Chile. Data included lifetime individual arsenic exposure estimates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…In this analysis, we assumed both a constant log-linear (log-transformed water As concentration) and a flexible non-linear (restricted cubic splines with knots at the 10th, 50th and 90th percentiles of log-transformed water As concentration) associations. The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this analysis, we assumed both a constant log-linear (log-transformed water As concentration) and a flexible non-linear (restricted cubic splines with knots at the 10th, 50th and 90th percentiles of log-transformed water As concentration) associations. The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73]. Furthermore, without available maxima values, the width of the highest concentration category was assumed to be equal to the next lowest category [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, diminished kidney clearance of arsenic and enhanced production of reactive oxygen species longitudinally contribute to perpetuate tissue insult and progression of chronic kidney disease [22,23]. Previous studies have also shown an association between arsenic and hypertension and type 2 diabetes mellitus, both suggesting additional mechanisms for secondary kidney damage [44,45]. Ecological studies from the United States, Chile, and Taiwan have shown that arsenic exposure is associated with increased mortality from kidney disease [13][14][15]22,26,28,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary exposure, including to As, may contribute to CVD and diabetes mortality risk in Hispanics/Latinos [3][4][5][6]. Hispanics/Latinos, who make up >15% of the United States (US) population, experience high mortality rates for cardiovascular disease (CVD) and diabetes [7,8].…”
Section: Introductionmentioning
confidence: 99%